Pontocerebellar hypoplasia type 6: A British case with PEHO-like features. - Rankin, J; Brown, R; Dobyns, W; Harington, J; Patel, J; Quinn, M; Brown, G (2010)
Six subtypes of autosomal recessive pontocerebellar hypoplasia (PCH) have been identified and the genetic basis of four of these (PCH1, PCH2, PCH4, and PCH6) is known. PCH6 is associated with cerebral atrophy and multiple but variable respiratory chain defects in muscle and has been reported in one consanguineous Sephardic Jewish family. It is caused by mutations in the RARS2 gene which encodes mitochondrial arginine-transfer RNA synthetase. Here we describe a female patient born to nonconsanguineous British parents. She presented in the neonatal period with increased respiratory rate, poor feeding and transiently elevated blood and CSF lactate levels. She went on to manifest profound developmental delay and severe microcephaly. Edema of the hands, feet, and face were suggestive of a PEHO-like condition (progressive encephalopathy, edema, hypsarrhythmia and optic atrophy), although optic atrophy and hypsarrhythmia were absent. Cranial MRI at age 14 months showed generalized cerebral atrophy, thinning of the pons and gross atrophy and flattening of the cerebellar hemispheres. Muscle biopsies on two occasions were normal with normal respiratory chain studies. Despite the absence of respiratory chain defects, the phenotype was felt to be consistent with PCH6 and indeed two novel pathogenic RARS2 mutations were identified. Ours is the second report of PCH6 due to RARS2 mutations and demonstrates that respiratory chain abnormalities are not obligatory, whereas some features of PEHO might be present.